Предмет: Алгебра,
автор: anastasia5552
вычислить (k^6-3d^2)^4
Ответы
Автор ответа:
0
Для вычисления необходимы значения k и d...))
(k⁶ - 3d²)⁴ = (k⁶)⁴ - 4(k⁶)³ * 3d² + 6(k⁶)² * (3d²)² - 4k⁶ * (3d²)³ + (3d²)⁴ =
= k²⁴ - 12k¹⁸d² + 54k¹²d⁴ - 108k⁶d⁶ + 81d⁶
(k⁶ - 3d²)⁴ = (k⁶)⁴ - 4(k⁶)³ * 3d² + 6(k⁶)² * (3d²)² - 4k⁶ * (3d²)³ + (3d²)⁴ =
= k²⁴ - 12k¹⁸d² + 54k¹²d⁴ - 108k⁶d⁶ + 81d⁶
Похожие вопросы
Предмет: Химия,
автор: nuralievanurgiza01
Предмет: Математика,
автор: ae3655331
Предмет: Информатика,
автор: kub0
Предмет: Биология,
автор: smyrfik666
Предмет: Математика,
автор: Аноним